ВЛИЯНИЕ КОМПЛЕКСНОЙ ПРОГРАММЫ ФИЗИЧЕСКОЙ РЕАБИЛИТАЦИИ НА ПОДРОСТКОВ С ОСТЕОХОНДРОЗОМ ПОЗВОНОЧНИКА INFLUENCE OF THE INTEGRATED PROGRAM PHYSICAL REHABILITATION FOR ADOLESCENTS WITH OSTEOCHONDROSIS OF THE SPINE - Самоленко, Т.В.; Гордийчук, Б.В. (Rehabilitation and Recreation, 2018)
В современном мире в связи с изменившимися условиями жизни (урбанизация, низкая двигательная активность, изменение режима и качества питания) остеохондрозом болеют от 40 до 80% жителей земного шара. Эффективность лечения зависит от своевременного начала и комплексности. С каждым годом количество больных увеличивается. И наиболее печально то, что остеохондроз «молодеет». Реабилитационные мероприятия в системе консервативного лечения имеют ряд существенных преимуществ и главное, будучи профилактическими, позволяют не использовать оперативное вмешательство, а стабилизировать патологические изменения позвоночника и даже уменьшить их. В статье показаны исследования, при использование комплексной программы физической реабилитации подростков с остеохондрозом позвоночника. Именно применение физических упражнений позволяют обеспечить активное сознательное участие самого больного в процессе реабилитации. In the modern society in connection with changed life’s conditions (urbanization, low motion activity, changes in diet and quality of products) from 40-80% of people over the world are suffering from osteochondrosis. Treatment’s efficiency depends on the timeliness of the beginning and it’s complexity. From year to year the amount of the sick is increasing. The worst fact is that osteochondrosis “is becoming younger”. Rehabilitation measures in the system of conservative treatment have a range of advantages and the most important is, while being profilactic, allows not to use the surgery interference, stabilize pathological changes of spine and even decrease them. There are researches in the article, in which complexive program of rehabilitation for children with spine osteochondrosis was used. The usage of physical exercises helps provide an active conscious participation of the sick person in the process of rehabilitation.